seni kaligrafi STRATEGI PENANAMAN NILAI KARAKTER KEPADA PESERTA DIDIK MELALUI KEGIATAN TULISAN SENI KALIGRAFI DI MADRASAH ALIYAH NEGERI MAN 4 MARTUBUNG - Asyifa Novianingtyas (Yayasan Haiah Nusratul Islam, 2026)
This study examines the implementation of calligraphy activities on educational values in the students of Madrasah Aliyah Negeri 4 Martubung. Calligraphy in Islam is not only an artistic expression, but also a medium of education and character building. This research uses a descriptive qualitative approach. Data collection techniques, observation techniques, interviews, and documentation. The data in this study uses triangulation techniques. The data analysis techniques in this study include data reduction, data presentation, and drawing conclusions. The results of the study show that calligraphy activities are carried out regularly as part of the madrasah extracurricular with the support of facilities and the guidance of experienced teachers. The educational values that develop through this activity include spiritual values, motor skills, discipline, patience, creativity, and appreciation for Islamic cultural heritage. The impact of calligraphy activities can be seen in increasing students' spirituality, character development, concentration skills, and sense of aesthetics. This study concludes that calligraphy is an effective means of forming Islamic characters and values in students, not only developing beautiful writing skills but also instilling comprehensive educational values. It is suggested that this activity continues to be developed with special training for teachers and the provision of more adequate media.